The lobby and the international relationships - Oliver González, Ana Belén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Review of bibliography on international relations and the influence of pressure groups on them. The relevance of lobbying and its interaction is analyzed. Study of the interdependence of lobbying in international relations through the review of existing concepts, combining bibliography on this interdependence in a single text with all the actors, all the theories, conceptions and ideas, from the 90's to the present. The research method is analytical, starting from general knowledge of a reality to make the distinction, knowledge and classification of the different essential elements that are part of it and the relationships they maintain with each other.